Glycine Protects H9C2 Cardiomyocytes from High Glucose- and Hypoxia/Reoxygenation-Induced Injury via Inhibiting PKCβ2 Activation and Improving Mitochondrial Quality - Yuan Zhang; Wating Su; Qiongxia Zhang; Jinjin Xu; Huimin Liu; Jun Luo; Liying Zhan; Zhongyuan Xia; Shaoqing Lei (Journal of Diabetes Research)
Background. Patients with diabetes are more vulnerable to myocardial ischemia reperfusion injury (IRI), which is involved in PKCβ2 activation and mitochondrial dysfunction. Glycine has been documented as a cytoprotective agent to attenuate diabetes-related abnormalities and reduce myocardial IRI, but the underlying mechanisms are still unclear. We determined whether glycine could attenuate high glucose- (HG-) and hypoxia/reoxygenation- (H/R-) induced injury by inhibiting PKCβ2 activation and improving mitochondrial quality in cultured H9C2 cells. Methods. H9C2 cells were either exposed to low glucose (LG) or HG conditions with or without treatment of glycine or CGP53353 (a selective inhibitor of PKCβ2) for 48 h, then subjected to 4 h of hypoxia followed by 2 h of reoxygenation (H/R). Cell viability, lactate dehydrogenase (LDH) release, mitochondrial membrane potential (MMP), superoxide dismutase (SOD) activity, and malondialdehyde (MDA) concentration were detected using corresponding commercial kits. Mitochondrial quality control-related proteins (LC-3II, Mfn-2, and Cyt-C) and PKCβ2 activation were detected by Western blot. Results. HG stimulation significantly decreased cell viability and SOD activity and increased LDH release, MDA production, and PKCβ2 activation as compared to LG group, all of which changes were further increased by H/R insult. Glycine or CGP53353 treatment significantly reduced the increase of LDH release, MDA production, PKCβ2 activation, and Cyt-C expression and the decrease of cell viability, SOD activity, MMP, Mfn-2 expression, and LC-3II/LC-3I ratio induced by HG and H/R stimulation. Conclusions. Supplementary glycine protects H9C2 cells from HG- and H/R-induced cellular injury by suppressing PKCβ2 activation and improving mitochondria quality.